Geochemical evaluation and driving factor analysis of soil salinization in Northeast China Plain - Dai, Huimin; Fang, Yunting; Chen, Chaoqun; Liu, Kai; Li, Xiao; Yang, Ze; Fang, Nana; Zhang, Yihe (Frontiers in Environmental Science, 2025)
IntroductionThe Songnen Plain in Northeast China is considered as one of the world's three major saline-alkali land regions. However, the evaluation of the extent and degree of saline-alkali land has primarily been mainly obtained via remote sensing interpretation, leading to inconsistencies in data on salinization levels and the area of saline-alkali land.MethodsRandom Forest-based modeling of total salt-exchangeable cation-chemical composition relationships facilitated high-precision spatial evaluation of soil salinization across Northeast China Plain.ResultsThe results show that: (1) Northeast China contains approximately 16.93 million hectares of salinized or alkalinized zonal soils, where pH and salinity levels demonstrate statistically significant positive correlations (p < 0.01) with concentrations of chloride (Cl), sodium (Na), magnesium (Mg), calcium (Ca), sulfur (S), and potassium (K). (2) Northeast China's Songliao Plain contains 6.92 million hectares of saline-alkali soils, exhibiting a distinct spatial gradient in soda salinization chemistry: from sulfate-dominated in the northeast, transitioning through chloride-sulfate composite zones, to carbonate and finally chloride-dominated types in the southwest. (3) Chloride and bicarbonate dominate the saline-alkali soils, primarily distributed in low plains (<200 m elevation) with distinct spatial zonation. (4) Since the 1980s, strongly alkaline soils (pH > 9.5) have expanded by 80,300 ha/year, accompanied by significant organic matter and nitrogen depletion.DiscussionResearch indicates that integrated topography-hydrogeology-climate factors drive soil salinization, while consistent and stable farming practices can mitigate its progression.